Greenhouse Tomato Producers’ Views on Soilless Agriculture in Antalya - Bilge Gözener; Halime Dereli (Turkish Journal of Agriculture: Food Science and Technology)
Tomato comes as the most commonly produced, consumed and subject for trading in the world. Alongside fresh consumption, on the other hand it forms the most significant raw material source of food industry, especially for tomato paste, frozen and dried vegetable-fruit and canned food industry. Turkey's greenhouse vegetable production field for 2016 year is 675173 decars and Antalya forms 51% of this field. Tomato forms 61.72% of Antalya's greenhouse production. The main material of the research consists of interviews made with producers resided in 5 villages/towns, where greenhouse tomato production is carried out densely in Antalya city, Alanya district. In 48 villages and towns, greenhouse tomato production is carried out, according to the official records. In the chosen areas, 365 producers exist. 20% of these producers (73) form the sample size. In the research, it was determined that the producers' average agricultural land possession is 9.13 decars and in 40.53% of these areas they grew tomatoes. None of these producers are engaged in contractual growing. All of the yield is produced for the edible (as table-top item). After the harvest, all of the products are sold in the wholesales market in county and city. 7.89% of the producers have no information on soilless agriculture, as 10.52% of them think that it has no advantages and 73.36% of them recommend traditional agriculture.